KEPUASAN KERJA KARYAWAN : STUDI LITERATUR - Pitasari, Nimas Ayu Aulia; Perdhana, Mirwan Surya (Faculty of Economics and Business Diponegoro University, 2018)
Job satisfaction considerably affects employee performance and employee outcome. This study aimed to present a literature review of the factors that affect employee satisfaction conditions and to cover the limitation of previous literature which is being research gaps of this study.Research method using systematic literature review. The research data was obtained through internet search on employee satisfaction journal published 2005-2017 key words using job satisfaction, employee satisfaction, employee job satisfaction, job satisfaction, job satisfaction among employee, job satisfaction, kepuasan kerja, and kepuasan kerja karyawan. The number of journals analyzed by 22 journals. Data were analyzed qualitatively.The result of the research is there are six factors that influence job satisfaction that is job content (autonomy and clarity of role), management (performance evaluation and management support), work environment (physical environment, supervisor's relationship with subordinate, and co-worker relationship), compensation reward), job promotion (promotion and employment system), and training (routine and effective training).